Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1017/s0266462304001278
|View full text |Cite
|
Sign up to set email alerts
|

Use of systematic reviews in the development of new provincial public health policies in Ontario

Abstract: Public health decision-makers in Ontario have very positive perceptions of the usefulness of systematic reviews in policy development. Therefore, ongoing efforts to promote the usefulness and relevance of systematic reviews to public health decision-makers should remain a priority for health services researchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 9 publications
2
35
0
Order By: Relevance
“…These results pose a challenge for future guideline development panels in the field of perioperative care. They should be aware of the identified barriers to implement recommendations into clinical practice,58–60 and the difficulty in bringing evidence into the field of decision and policy making 61 62…”
Section: Discussionmentioning
confidence: 99%
“…These results pose a challenge for future guideline development panels in the field of perioperative care. They should be aware of the identified barriers to implement recommendations into clinical practice,58–60 and the difficulty in bringing evidence into the field of decision and policy making 61 62…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, evidence from systematic reviews has been found to be used infrequently by WHO policy-makers. 12 Dobbins and colleagues 13 observed that, although systematic reviews were used in making guidelines for public health in Ontario, the recommendations were not adopted at the level of policy.…”
Section: Why Is It Important?mentioning
confidence: 99%
“…Likewise, one Canadian study which surveyed Ontarian policymakers on several occasions during a 5 year period, concluded that organisational culture had become more supportive of systematic reviews (Dobbins et al, 2004). This suggests that some…”
Section: <Please Insert Table 3 Here>mentioning
confidence: 99%